2019
DOI: 10.1029/2018jc014230
|View full text |Cite
|
Sign up to set email alerts
|

Why Gliders Appreciate Good Company: Glider Assimilation in the Oregon‐Washington Coastal Ocean 4DVAR System With and Without Surface Observations

Abstract: Gliders are low-power autonomous underwater vehicles used to obtain oceanic measurements in vertical sections. Assimilation of glider temperature and salinity into coastal ocean circulation models holds the potential to improve the ocean subsurface structure estimate. In this study, the impact of assimilation of glider observations is studied using a four-dimensional variational (4DVAR) data assimilation and forecast system set offshore of Oregon and Washington on the U.S. West Coast. Four test cases are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The work by Pasmans et al. (2019), in which the reanalysis using the combination of surface and glider observations was skillful in estimating and forecasting the subsurface ocean features, has demonstrated that assimilating glider observations without the surface observations can create erroneous eddy variability that will deteriorate forecast performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Pasmans et al. (2019), in which the reanalysis using the combination of surface and glider observations was skillful in estimating and forecasting the subsurface ocean features, has demonstrated that assimilating glider observations without the surface observations can create erroneous eddy variability that will deteriorate forecast performance.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that the glider observations should be used with caution. The work by Pasmans et al (2019), in which the reanalysis using the combination of surface and glider observations was skillful in estimating and forecasting the subsurface ocean features, has demonstrated that assimilating glider observations without the surface observations can create erroneous eddy variability that will deteriorate forecast performance. shows that the sharper across-current vorticity gradient within the EAC leads in turn to more intense submesoscale features growing on its inshore side.…”
Section: Eddies and Submesoscale Variabilitymentioning
confidence: 99%
“…A final way to compare the system is to give more weight on some specific physical structures, for example the formation of an eddy between August-December 2017 in the Balearic Sea (Aguiar et al, 2019). This is a good testbed to assess the gain from glider observations which are prone to generate eddy-like structures in the analysis (Pasmans et al, 2019). In these experiments, the initial condition (IC) used for the forecast, which is normally the best estimate available (i.e., analysis state), is perturbed by using analysis fields from the preceding 10-days.…”
Section: Deliverablesmentioning
confidence: 99%
“…For example, Spray gliders operating in the California Underwater Glider Network (CUGN) have made sustained observations along three lines in the CCS since 2007 (Rudnick et al 2017) and have been used to study the impacts of the 2014-15 marine heat wave (Zaba and Rudnick 2016) and the El Niño of 2015-16 (Jacox et al 2016). Glider observations are also particularly useful for constraining data assimilating models, and it has been demonstrated that assimilating glider data can significantly improve model forecasting capabilities (Pasmans et al 2019). Biogeochemical sensors have been equipped onto gliders to measure parameters such as O 2 (Pierce et al 2012), nitrate (Evans et al 2013;Vincent et al 2018), bio-optics (Briggs et al 2011), and zooplankton (Ohman et al 2019).…”
Section: Introductionmentioning
confidence: 99%